Faktor yang Mempengaruhi Kecemasan Keluarga dalam Merawat Anggota Keluarga dengan TB Paru - Verawati Rade Taka; Febriany Mamo Kitu, Irene; Toru, Veronika (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Pulmonary tuberculosis is a chronic, recurrent infectious disease that usually affects the lungs, and can even affect all organs. Pulmonary TB is spread through the air from person to person. When a person with pulmonary TB coughs, sneezes, or spits, TB germs are released into the air, which can be inhaled by others, potentially infecting them. Psychological distress in families with members with pulmonary TB can also occur due to fear of contracting TB, worry about the lengthy treatment process, and even concern about the social environment where negative stigma toward pulmonary TB persists. This literature review was conducted by searching the Google Scholar database and selecting articles based on inclusion criteria, resulting in the selection of 10 primary articles for analysis. Family anxiety in caring for a family member with pulmonary TB is a manifestation of multiple psychological burdens. The majority of families indicated that despite having the resilience to care, they remain emotionally distressed. Family anxiety in caring for a patient with pulmonary TB is a complex phenomenon triggered by a combination of a lack of accurate medical information, economic pressures, gender, age, and minimal social support in the surrounding environment. Education should not only focus on patient medication schedules but also address family anxiety management. Furthermore, it's crucial for healthcare facilities to initiate support groups for patient families to share emotional burdens and prevent caregivers from feeling socially isolated.Keywords: abstract keywords